Population dynamics of Encrasicholina devisi and Stolephorus insularis (Teleostei: Engraulidae) in Tegal Waters, Indonesia - BETA INDI SULISTYOWATI; DIAN WIJAYANTO; AGUS HARTOKO; PUJIONO WAHYU PURNOMO (Society for Indonesian Biodiversity, 2026)
Abstract. Sulistyowati BI, Wijayanto D, Hartoko A, Purnomo PW. 2026. Population dynamics of Encrasicholina devisi and Stolephorus insularis (Teleostei: Engraulidae) in Tegal Waters, Indonesia. Biodiversitas 27 (3): d270319. https://doi.org/10.13057/biodiv/d270319. Devis anchovy (Encrasicholina devisi) and Hardenberg's anchovy (Stolephorus insularis) are small pelagic fish with strong market demand in Tegal Waters, Indonesia. The study was performed to examine the population dynamics of the anchovies based on data from fish catches from April 2024 to March 2025. A total 9,546 samples (6,294 E. devisi and 3,252 S. insularis) were used in this study. Fish length and total weight were measured to determine growth and exploitation, using von Bertalanffy’s equation for growth parameters and the Beverton and Gulland’s equations for mortality and exploitation rates. The growth analysis indicated maximum lengths (L∞) of 103.81 mm for E. devisi and 49 mm for S. insularis, with growth coefficients (K) of 2.5 and 1.6/year, respectively. Both species were categorized as overexploited. Therefore, catch quotas need to be applied in order to ensure the fish sustainability. The maximum sustainable yields (CMSY) of 485.6739 tons and 85.8343 tons have generated economic values of IDR 5.8 billion (USD 341,417) and IDR 3.7 billion (USD 217,800), respectively. The sustainable management measures include reducing fishing effort by 30-40%, increasing mesh size by 1-2 mm, adopting a 1-2 months restricted season, and reducing total capture to 60-70% of current levels, with a stricter reduction for E. devisi than S. insularis.